Factors influencing adherence to treatment among people with leprosy in Costa Rica - Rivera Chavarría, Ana Leonor (2023)
La Dra. Ana Leonor Rivera Chavarría es docente en la Escuela de Medicina en la Universidad de Costa Rica.